CONSERVATÓRIO DE MÚSICA DE PONTA GROSSA: (RE) PRODUÇÃO CULTURAL E DISTINÇÃO SOCIAL (1971-1995) - Vendrami, Georgeana Lanzini (2010)
This dissertation analyses the cultural and educational project represented by the Maestro Paulino Martins Alves Musical and Dramatic Conservatory (CDM) in the period between 1971 and 1995, focusing on aspects related to the foundation of this institution and on the social (intellectual) agents responsible for it. The analysis draws on Cultural History authors in order to put into discussion the written and oral sources of the documentary corpus that, associated to the history of music teaching in Brazilian and European conservatories and to discussions on the nature of the educational process of such institutions, is used to econstruct both the institutional history of the CDM and the music education experiences carried out within this cultural space. In the light of considerations by Pierre Bourdieu related to art history and cultural/symbolic struggles present in society, it is possible to affirm that the groups that worked at the CDM established a view of art, music and music education that induced a disposition or aesthetic habitus amongst those who consumed such cultural goods. Furthermore, such groups used this symbolic capital as a strategy to be recognised as a distinguished social stratum in the city of Ponta Grossa.